Resin sheet for sealing hollow electronic components and hollow electronic components
A resin composition with a thermosetting resin, polyfunctional maleimide, benzoxazine, and epoxy resin addresses the flexibility and thermal expansion trade-off, offering superior sealing and protection for hollow electronic components with reduced material waste and improved productivity.
Patent Information
- Application Number
- JP2025062774
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2025-11-06
- Estimated Expiration
- 2045-04-04
AI Technical Summary
Resin sheets for sealing hollow electronic components face a trade-off between flexibility and thermal expansion, with existing materials lacking sufficient flexibility and exhibiting high thermal expansion, leading to potential cracks in solder joints.
A resin composition comprising a thermosetting resin, polyfunctional maleimide compound, benzoxazine compound, and epoxy resin, with optional inorganic filler, which achieves a balance of flexibility and low thermal expansion, allowing for uniform coverage of components with varying shapes and preventing solder cracks.
The resin sheet provides excellent flexibility, low thermal expansion, and strong adhesion, ensuring effective sealing and protection of electronic components while maintaining a hollow structure, reducing material waste and improving productivity.
Smart Images

Figure 0007764986000001_ABST
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to a resin sheet for sealing a hollow electronic component and a hollow electronic component. [Background technology]
[0002] Hollow electronic components such as SAW filters, which are capable of passing only signals of a specific frequency and cutting noise, are provided with a sealing layer to protect the electronic components from physical impacts, temperature changes, etc. The sealing layer is required to seal the electronic components while maintaining the hollow structure between the electronic components and the substrate. As the sealing layer, many heat-meltable resin sheets have been developed that easily maintain a hollow structure and have excellent dimensional stability.
[0003] Patent Document 1 discloses a resin sheet for hollow cavity sealing that contains 70 to 90% by volume of an inorganic filler and has physical property values such as a linear expansion coefficient within specific ranges. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2014-209568 Summary of the Invention [Problem to be solved by the invention]
[0005] Resin sheets for sealing hollow electronic components are required to have flexibility that allows them to stretch so that they can uniformly cover electronic components of various shapes with different heights. Furthermore, resin sheets for sealing hollow electronic components are required to have low thermal expansion in order to prevent cracks from occurring in the solder that joins the substrate and the electronic components.
[0006] The flexibility and thermal expansion mentioned above are usually in a trade-off relationship, and although the resin sheet described in Patent Document 1 has low thermal expansion, it contains a large amount of inorganic filler, and therefore its flexibility is sometimes insufficient.
[0007] The present disclosure has been made in consideration of the above-mentioned problems, and an object of the present disclosure is to provide a resin sheet for sealing hollow electronic components that can achieve both excellent flexibility and low thermal expansion, and a hollow electronic component using the same. [Means for solving the problem]
[0008] As a result of extensive research, the present inventors have found that the problems of the present disclosure can be solved in the following aspects, and have thus completed the present disclosure. [1] A resin sheet for sealing hollow electronic components, for forming a sealing layer for a hollow electronic component, the resin sheet being a resin composition containing a thermosetting resin (A), a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D). [2] The resin sheet for sealing hollow electronic components according to [1], wherein the total content of the polyfunctional maleimide compound (B) having two or more maleimide groups, the benzoxazine compound (C), and the epoxy resin (D) in the resin composition is 5 to 180 parts by mass per 100 parts by mass of the thermosetting resin (A). [3] The resin sheet for sealing hollow electronic components according to [1] or [2], wherein the resin composition further contains an inorganic filler (E), and the inorganic filler (E) contains silica particles. [4] The resin sheet for sealing hollow electronic components according to [3], wherein the content of the inorganic filler (E) in the resin composition is 5 to 70 mass %. [5] The resin sheet for sealing hollow electronic components according to any one of [1] to [4], wherein the resin sheet is cured at 180°C for 2 hours, and the cured product has a linear expansion coefficient at 150 to 200°C of 3 to 750 ppm / K. [6] The resin sheet for sealing hollow electronic components according to any one of [1] to [5], which has a breaking elongation at 100°C of 300 to 2000%. [7] The resin sheet for sealing hollow electronic components according to any one of [1] to [6], wherein the resin sheet is bonded to a polyimide substrate and cured at 180°C for 2 hours, and the cured product has an adhesive strength at 25°C of 0.6 to 40 N / cm. [8] A hollow electronic component comprising: a substrate; an electronic component mounted on the substrate; and a sealing layer that seals the electronic component while maintaining a hollow structure between the substrate and the electronic component, wherein the sealing layer is formed from a cured product of the resin sheet for sealing hollow electronic components according to any one of [1] to [7]. [Effects of the Invention]
[0009] The present disclosure has the excellent effect of providing a resin sheet for sealing hollow electronic components that can achieve both excellent flexibility and low thermal expansion, and a hollow electronic component using the same. [Brief explanation of the drawings]
[0010] [Figure 1] 1A to 1C are schematic cross-sectional views showing two examples of hollow electronic components according to an embodiment of the present invention. [Figure 2] FIG. 2 is a schematic diagram of a test substrate of this example. DETAILED DESCRIPTION OF THE INVENTION
[0011] Hereinafter, a resin sheet for sealing a hollow electronic component and a hollow electronic component using the same according to the present disclosure will be described in detail. It should be noted that other embodiments are also included within the scope of the present disclosure as long as they are consistent with the spirit of the present disclosure. In this specification, a numerical range specified using "to" includes the numerical values before and after "to" as the lower and upper limits. In the present specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range. In addition, in the present specification, the upper or lower limit of a numerical range may be replaced with a value shown in the examples. Unless otherwise noted, each component in this specification may be used independently, either singly or in combination of two or more. The numerical values described in this specification refer to values obtained by the methods described in the Examples below.
[0012] 1.Resin sheets for sealing hollow electronic components The resin sheet for sealing hollow electronic components disclosed herein (hereinafter also referred to as the present resin sheet) is a sheet suitable for forming a sealing layer that seals hollow electronic components (for sealing hollow electronic components). As shown in FIG. 1(a), a hollow electronic component (hollow device) includes a substrate 1, an electronic component 2 mounted on the substrate 1, and a sealing layer 4 that seals the electronic component 2 while maintaining a hollow structure 3 (hollow portion) between the substrate 1 and the electronic component 2. Thus, in the hollow electronic component 10, electronic components 2 of various shapes, including height variations, are uniformly covered by the sealing layer 4 while maintaining the hollow structure 3 between the substrate 1 and the electronic component 2. Thus, the present resin sheet has the advantage of being able to simultaneously seal multiple electronic components 2 formed on a substrate 1 or the like. Naturally, the present resin sheet may also be used to seal a single electronic component (semiconductor element). Furthermore, as shown in FIG. 1(b), the electronic component 2 may be secondary-sealed by a second sealing layer 5 provided on the primary sealing layer (first sealing layer) 4. In this way, the hollow electronic component according to the present disclosure may have a second sealing layer 5 formed on a sealing layer (first sealing layer) 4, and the electronic component may be sealed with multiple sealing layers. Figures 1(a) and 1(b) are schematic cross-sectional views showing two examples of a hollow electronic component 10 according to this embodiment. Reference numeral 6 denotes, for example, a lead-free solder ball that joins the substrate 1 and the electronic component 2.
[0013] The resin sheet is a resin composition containing a thermosetting resin (A), a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D). When the resin sheet encapsulates an electronic component 2 while maintaining its hollow structure, it is converted into a cured encapsulating layer 4. The resin sheet may be a single layer or a multilayer. In the case of a multilayer, layers of the same and / or different resin compositions are laminated. Hereinafter, the thermosetting resin (A), the polyfunctional maleimide compound (B) having two or more maleimide groups, the benzoxazine compound (C), the epoxy resin (D), and the inorganic filler (E) described below will also be referred to as components (A) to (E), respectively. The second encapsulating layer 5 described above may contain these components and may satisfy the configuration of the resin sheet.
[0014] As described above, the resin sheet has excellent flexibility and is therefore suitable for use in forming a sealing layer 4 on an unsealed electronic component 2 while maintaining the hollow structure 3. Furthermore, the resin sheet is lightweight, offers high design flexibility, and can be integrated into complex shapes, making it suitable for use in mounting multiple encapsulated semiconductor chips on a substrate and encapsulating them all at once. Furthermore, the resin sheet has low thermal expansion, which can prevent solder cracks from occurring when the resin sheet is used to form a hollow electronic component.
[0015] In this specification, the electronic component 2 is incorporated into an electric circuit or electronic device to control an electric signal, and may include the following semiconductor elements: The semiconductor elements include power semiconductor elements such as an IGBT (Insulated Gate Bipolar Transistor), a MOSFET (Metal Oxide Semiconductor Field Effect Transistor), a SAW filter (Surface Acoustic Wave Filter), a bipolar transistor, and a diode; light-emitting elements such as LEDs; optical semiconductor elements such as light-receiving elements; semiconductor integrated circuits formed on a semiconductor substrate such as a silicon substrate; and semiconductor chips obtained by separating semiconductor integrated circuits formed on a semiconductor substrate. This resin sheet allows for lightweight construction and integration of complex shapes, offers high design freedom, and has excellent dielectric properties, making it suitable for use in the information and communications field.Electronic components such as semiconductor elements are usually formed or mounted on the top surface of a base substrate.
[0016] In the present disclosure, encapsulation refers to using the present resin sheet to cover an object (e.g., a substrate 1 and an electronic component 2) while maintaining the hollow structure 3, and then curing the sheet to form an encapsulating layer 4. The encapsulating layer 4 of the present disclosure encompasses all modes in which the electronic component 2 is covered with the encapsulating layer 4, including modes in which the electronic component 2 is directly encapsulated, as well as modes in which a semiconductor module or the like in which the electronic component 2 is encapsulated is further encapsulated. Among these modes, the present resin sheet has excellent flexibility, low thermal expansion, and excellent adhesive strength and heat resistance, and is therefore particularly suitable for use in modes in which the resin sheet encapsulates the electronic component 2 while preventing it from lifting or peeling off from the substrate 1.
[0017] The linear expansion coefficient and adhesive strength of the present disclosure are evaluated under conditions for a fully cured stage, i.e., a resin sheet cured (heated) at 180°C for 2 hours. The term "fully cured stage" may refer to a cured product as well as a product in the process of curing. In this specification, a cured product refers to a product that has been cured to the extent that further heating does not substantially promote the curing reaction, and the sealing layer is considered a (fully) cured product. A resin sheet that may undergo a partial curing reaction during formation but may be cured by further heating is not considered a (fully) cured product. The resin composition (thermosetting resin composition) may also be in a B-stage state in which some of its components are semi-cured. A cured resin composition is typically obtained by heat treatment at 100 to 180°C for 30 minutes to 5 hours. As described above, the present resin sheet may include a resin sheet before it is completely cured, more specifically, an uncured resin sheet and a semi-cured resin sheet. Furthermore, the cured resin sheet of the present resin sheet means a resin sheet that has been completely cured.
[0018] The resin sheet is cured at 180°C for 2 hours, and the cured product preferably has a coefficient of linear expansion (CTE) at 150 to 200°C of 3 to 750 ppm / K. A coefficient of linear expansion of 3 ppm / K or more can reduce the difference in linear expansion between the resin sheet and the substrate or electronic components, even when the package structure after the sealing process is subjected to high-temperature treatment, making it possible to easily prevent warpage of the substrate. From the same perspective, the coefficient of linear expansion is more preferably 5 ppm / K or more, even more preferably 50 ppm / K or more, and particularly preferably 120 ppm / K or more. A coefficient of linear expansion of 750 ppm / K or less provides even better solder crack resistance. From the same perspective, the coefficient of linear expansion is more preferably 500 ppm / K or less, even more preferably 300 ppm / K or less, and particularly preferably 200 ppm / K or less. The method for measuring the coefficient of linear expansion will be described later. The linear expansion coefficient can be adjusted by changing the types of components (B) to (E) in the resin composition or adjusting the amounts added. More specifically, it is believed that the rigid molecular structure of the polyfunctional maleimide compound (B), the stabilization of the structure by hydrogen bonds formed within the molecule of the benzoxazine compound (C), the increase in crosslink density by the epoxy resin (D), and the high loading of the inorganic filler (E) contribute to the reduction in the linear expansion coefficient.
[0019] The resin sheet (before curing) preferably has a breaking elongation at 100°C of 300 to 2000%. A breaking elongation of 300 to 2000% provides superior coverage of recesses formed by the mounting of electronic components. More specifically, a breaking elongation of 300% or greater maintains appropriate breaking strength while maintaining a moderate deformation force, significantly reducing defects such as cracks and breaks in the sealing layer. From the same perspective, the breaking elongation is more preferably 500% or greater, even more preferably 900% or greater, and particularly preferably 1200% or greater. Furthermore, a breaking elongation of 2000% or less can easily prevent the resin sheet from penetrating hollow portions. From the same perspective, the breaking elongation is more preferably 1800% or less, even more preferably 1600% or less, and particularly preferably 1500% or less. In addition, when the resin sheet has anisotropy in elongation, the direction with the lowest elongation is set to 300% or more, and the direction with the highest elongation is set to 2000% or less. The method for measuring the breaking elongation will be described later. The breaking elongation can be adjusted by changing the types of components (A) to (E) in the resin composition or adjusting the amounts added. More specifically, the introduction of a rigid skeleton such as a polyfunctional maleimide compound (B) or the incorporation of an inorganic filler (E) tends to increase the elasticity of the resin sheet and decrease the breaking elongation. On the other hand, the addition of a thermoplastic resin or an epoxy resin (D) with a low melting temperature tends to soften the resin when heated and increase its flexibility. Furthermore, the benzoxazine compound (C) undergoes B-stage crosslinking with the curing agent or resin to increase its molecular weight, which tends to increase the breaking elongation.
[0020] The adhesive strength of the cured product obtained by bonding the resin sheet to a polyimide substrate and curing (heating) it at 180°C for 2 hours at 25°C is preferably 0.6 to 40 N / cm. If the adhesive strength is 0.6 N / cm or more, lifting and peeling of the resin sheet from the adherend can be easily prevented during a thermal shock test. From the same perspective, the adhesive strength is more preferably 0.9 N / cm or more, even more preferably 1.2 N / cm or more, and particularly preferably 1.5 N / cm or more. Furthermore, if the adhesive strength is 40 N / cm or less, the resin sheet can be easily peeled back when analyzing processing defects or failures, facilitating reprocessing and component recovery. From the same perspective, the adhesive strength is more preferably 25 N / cm or less, even more preferably 15 N / cm or less, and particularly preferably 10 N / cm or less. The adhesive strength can be adjusted by adjusting the amounts of components (B) to (E) added to the resin composition and the film thickness of the resin sheet. More specifically, increasing the amount of the polyfunctional maleimide compound (B), benzoxazine compound (C), and epoxy resin (D) increases the crosslink density within the resin sheet, tending to increase the adhesive strength. On the other hand, increasing the amount of inorganic filler (E) tends to impair anchoring to the substrate, and decrease the adhesive strength. Furthermore, reducing the film thickness of the resin sheet tends to increase the stress generated at the adhesive interface, decreasing the adhesive strength.
[0021] From the viewpoint of heat resistance, the Tg of the resin sheet after heating at 180°C for 2 hours is preferably 20 to 200°C. The lower limit of the Tg is more preferably 25°C, even more preferably 30°C, and particularly preferably 40°C. The upper limit of the Tg is more preferably 190°C, even more preferably 180°C, and particularly preferably 170°C. The Tg of the resin sheet can be adjusted by adjusting the amounts of components (B) to (E) added to the resin composition. Specifically, increasing the amount of the polyfunctional maleimide compound (B), benzoxazine compound (C), or epoxy resin (D) increases the rigid molecular structure in the resin sheet, and further increases the crosslink density, thereby increasing the Tg.
[0022] The thickness of the resin sheet can be appropriately designed within a range that achieves the effects of the present disclosure. For example, the thickness of the resin sheet can be set to 1 to 1,000 μm. From the viewpoints of coverage and ease of handling, a thickness of 5 to 300 μm is preferred, and 10 to 100 μm is more preferred. By setting the thickness of the resin sheet to 1 μm or more, the pressure during the pressing process can be diffused within the resin sheet, making it possible to easily achieve sufficient coverage. By setting the thickness of the resin sheet to 1,000 μm or less, it is possible to further increase the degree of design freedom. Furthermore, the resin sheet absorbs little pressure loss from the pressure applied during the pressing process, allowing the resin (A) and other components to flow sufficiently, making it possible to easily achieve excellent coverage.
[0023] Conventionally, encapsulants such as encapsulants have been used as the sealing layer 4, but this has sometimes led to productivity issues. For this reason, when using a coating type such as a resin sheet, i.e., when the sealing layer 4 is coated to conform to the shape of the electronic component 2, gaps are likely to form between the adherend and the coating layer at uneven corners formed by mounting the electronic component 2, particularly at right angles, and further gaps are likely to form over time, which can cause storage stability problems.
[0024] However, with the present resin sheet, the encapsulating layer 4 can be formed simultaneously along electronic components 2 of various shapes and height variations, thereby reducing material waste in the resin sheet. Furthermore, the ability to coat electronic components simultaneously significantly increases productivity and design flexibility. Furthermore, by including the specific material described below, the present resin sheet significantly reduces gaps that occur at corners (especially at right-angled or other shaped portions) between the adherend (electronic component 2) and the coating layer, achieving excellent coating properties. After forming the encapsulating layer 4, other functional layers, such as a conductive layer, may be further coated. Since functional layers can be stacked using the same equipment, productivity is excellent.
[0025] The present resin sheet may be used as a laminated sheet in which one or more functional sheets are laminated on the present resin sheet. The functional sheet is not particularly limited. Specific examples of functional sheets include electromagnetic wave shielding sheets, thermally conductive sheets that dissipate heat from semiconductor elements, shielding sheets that prevent the semiconductor elements from being seen or that block light, moisture-proof sheets that protect the semiconductor elements from moisture, decorative sheets, flame-retardant sheets that have been imparted with flame retardancy, protective sheets that have been imparted with hard coating properties, bonding sheets that improve bonding to semiconductor elements, etc., and functional sheets that are any combination of these. A functional layer can be formed by coating the present resin sheet with a functional sheet.
[0026] 1(b), the present resin sheet (sealing layer 4) may be coated with a second sealing layer 5 in the form of, for example, a tablet, liquid, granules, or sheet, to secondary seal the substrate 1 and electronic component 2. For the second sealing layer 5, for example, a conventionally known sealing material composed of an epoxy resin, a curing agent, an inorganic filler, a curing catalyst, a coupling agent, a flame retardant, a colorant, etc. may be used as appropriate. Furthermore, as described above, the second sealing layer 5 may have the same configuration as the present resin sheet.
[0027] The resin sheet can be produced by any conventional method, and for details, see the examples below.
[0028] 1-1.Resin composition The resin sheet is a resin composition (hereinafter also referred to as the present composition) containing a thermosetting resin (A), a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D). It is preferable that these components in the resin composition mutually cure upon heat treatment. Note that the resin composition may be partially cured at the stage of the present resin sheet.
[0029] 1-1a.Thermosetting resin (A) The thermosetting resin (A) functions as a binder to adhere and fix the adherend. The thermosetting resin (A) may contain a thermoplastic resin, a photocurable resin, etc. in addition to the thermosetting resin, or may be composed solely of a thermosetting resin, so long as it has thermosetting properties as a whole. The thermosetting resin is a resin having multiple functional groups that can be used in a crosslinking reaction by heating, and may also have functional groups that are capable of self-crosslinking.
[0030] The functional group of the thermosetting resin may be appropriately selected depending on the combination with other components described below, and examples thereof include a hydroxyl group, a carboxyl group, an amino group, an epoxy group, an oxetanyl group, an oxazoline group, an oxazine group, an aziridine group, a thiol group, an isocyanate group, a blocked isocyanate group, and a silanol group. From the viewpoint of reactivity, the functional group is preferably a carboxyl group, a hydroxyl group, or an epoxy group.
[0031] The acid value of the thermosetting resin is preferably 1 to 30 mgKOH / g, more preferably 2 to 20 mgKOH / g, and even more preferably 3 to 15 mgKOH / g. By setting the acid value of the thermosetting resin to 1 mgKOH / g or more, the crosslink density with other components can be optimized while maintaining good intermolecular forces with adherends such as electronic components, thereby further improving sealing properties. Furthermore, by setting the acid value of the thermosetting resin to 30 mgKOH / g or less, the intermolecular forces with adherends such as electronic components can be maintained good while further improving adhesion.
[0032] The content of the thermosetting resin (A) in the resin sheet (solid content) is preferably 20 to 50% by mass. Examples of the thermosetting resin (A) include amide resins, imide resins, (meth)acrylic resins, maleic acid resins, butadiene resins, urethane resins such as urethane resins and urethane urea resins, oxetane resins, phenoxy resins, polyamide-imide resins, alkyd resins, amino resins, polylactic acid resins, oxazoline resins, benzoxazine resins, silicone resins, and fluororesins. Among these, the thermosetting resin (A) preferably contains a urethane resin including a urethane resin and / or a urethane urea resin. These resins may be any known resin, and commercially available products may be used.
[0033] The weight-average molecular weight (Mw) of the thermosetting resin (A) can be appropriately designed, but is preferably 10,000 to 1,000,000 from the viewpoint of increasing the mechanical strength of the sealing layer and enhancing the storage stability of the resin sheet. From the viewpoint of durability and adhesion, a value of 25,000 to 300,000 is more preferable, and a value of 50,000 to 200,000 is even more preferable. The ratio of the number-average molecular weight (Mn) to Mw (Mw / Mn), which indicates the degree of dispersion of the thermosetting resin (A), is preferably 1.0 to 17, more preferably 1.5 to 14, and even more preferably 2.0 to 10. By setting the Mw / Mn ratio to 1.0 to 17, the fluidity of the resin can be more easily controlled, resulting in improved coating properties. Furthermore, the rate at which the resin wets the adherend is made uniform, thereby further improving adhesion.
[0034] The urethane resin can be designed appropriately and is not limited. However, a urethane resin (A1) containing a structural unit derived from at least one polyol selected from dimer diol and trimer triol, and / or a structural unit derived from at least one polyamine selected from dimer diamine and trimer triamine, and having a urethane bond and optionally a urea bond, is preferred. Hereinafter, structures derived from these structural units are collectively referred to as "dimer structures." The urethane bond is formed by the reaction of a hydroxy group with an isocyanate group, and the urea bond is formed by the reaction of an amino group with an isocyanate group. Urethane resins are obtained by urethane bonding between reaction components containing two or more polyol components per molecule and a polyisocyanate component having two or more isocyanate groups per molecule. Urethane urea resins are obtained, for example, by reacting a urethane prepolymer with terminal isocyanates, obtained by the reaction of a polyol with a polyisocyanate, with a chain extender such as a polyamine component having two or more amino groups per molecule.
[0035] The use of a urethane resin (A1) having a dimer structure and a urethane bond or a combination of a urethane bond and a urea bond provides excellent flexibility and an appropriate elongation at break of the resin sheet, resulting in excellent sealing properties. Furthermore, the unshared electron pairs of the nitrogen atoms contained in the urethane bonds prevent the sealing layer from breaking or rupturing, thereby achieving not only excellent coating properties but also strong adhesive strength to the adherend.
[0036] 1-1b. Polyfunctional maleimide compounds (B) The polyfunctional maleimide compound (B) is a compound having two or more maleimide groups, and can be represented by the following general formula (1). [ka] In formula (1), R 1 is a k-valent organic group, and R 2 , R 3 is a hydrogen atom or a monovalent organic group. The organic group may be a hydrocarbon group composed only of C and H, or may be a group containing, in addition to C and H, heteroatoms such as N, O, and S, or halogen atoms. k is an integer of 2 or more, and an integer of 2 to 10 is preferred. R 2 ,R 3 may be the same group or different groups.
[0037] In formula (1), R 1 Examples of the alkylene group include an alkylene group and an arylene group. Examples of the alkylene group include those having 1 to 20 carbon atoms. Examples of the alkylene group include a chain alkylene group and a cyclic alkylene group. The chain alkylene group may be either linear or branched. Examples of the chain alkylene group include a methylene group, an ethylene group, and a hexamethylene group. Examples of the arylene group include those having 1 to 20 carbon atoms. Examples of the arylene group include a phenylene group and a methylphenylene group.
[0038] In formula (1), R 2 , R 3 Examples of the organic group include alkyl groups and aryl groups having 1 to 20 carbon atoms. Examples of the alkyl group include a methyl group, an ethyl group, and a propyl group. Examples of the aryl group include a phenyl group, a substituted phenyl group, a naphthyl group, and a substituted naphthyl group.
[0039] Examples of such polyfunctional maleimide compounds include N,N'-ethylene bismaleimide, N,N'-hexamethylene bismaleimide, N,N'-(1,3-phenylene) bismaleimide, N,N'-[1,3-(2-methylphenylene)] bismaleimide, N,N'-(1,4-phenylene) bismaleimide, bis(4-maleimidophenyl)methane, bis(3-methyl-4-maleimidophenyl)methane, bis(4-maleimidophenyl)methane, bis(4-maleimidophenyl) ether, bis(4-maleimidophenyl sulfone, bis(4-maleimidophenyl) sulfide, bis(4-maleimidophenyl) ketone, bis(4-maleimidocyclohexyl)methane, 1,4-bis(4-maleimidophenyl)cyclohexane, 1,4-bis(4-maleimidomethyl)cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(3-maleimidophenoxy)benzene, Bis[4-(4-maleimidophenoxy)phenyl]methane, 1,1-bis[4-(3-maleimidophenoxy)phenyl]ethane, 1,1-bis[4-(4-maleimidophenoxy)phenyl]ethane, 1,2-bis[4-(3-maleimidophenoxy)phenyl]ethane, 1,2-bis[4-(4-maleimidophenoxy)phenyl]ethane, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 2,2 -bis[4-(3-maleimidophenoxy)phenyl]butane, 2,2-bis[4-(3-maleimidophenoxy)phenyl]butane, 2,2-bis[4-(3-maleimidophenoxy)phenyl]-1,1,1,3,3,3 hexafluoropropane, 2,2-bis[4-(4-maleimidophenoxy)phenyl]1,1,1,3,3,3 hexafluoropropane, 4,4'-bis(3-maleimidophenoxy)biphenyl, 4,4'-Bis(4-maleimidophenoxy)biphenyl, bis[4-(3-maleimidophenoxy)phenyl]ketone, bis[4-(4-maleimidophenoxy)phenyl]ketone, bis[4-(3-maleimidophenoxy)phenyl]sulfide, bis[4-(4-maleimidophenoxy)phenyl]sulfide, bis[4-(3-maleimidophenoxy)phenyl]sulfoxide, bis[4-(4-(maleimidophenoxy)phenyl]sulfoxide, bis[4-(3-maleimidophenoxy)phenyl]sulfone, bis[4-(4-maleimidophenoxy)phenyl]sulfone, bis[4-(3-maleimidophenoxy)phenyl]ether, bis[4-(4-maleimidophenoxy)phenyl]ether, 1,4-bis[4-(4-maleimidophenoxy)-α,α-dimethyl Benzene], 1,3-bis[4-(4-maleimidophenoxy)-α,α-dimethylbenzene]benzene, 1,4-bis[4-(3-maleimidophenoxy)-α,α-dimethylbenzene]benzene, 1,3-bis[4-(3-maleimidophenoxy)-α,α-dimethylbenzene]benzene, 1,4-bis[4-(4-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene, 1,3-bis[4(4-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene, 1,4-bis[4-(3-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene, 1,3-bis[4-(3-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene, and the like can be mentioned.
[0040] Furthermore, examples of the polyfunctional maleimide compound (B) include not only the non-polymers described above but also polymers represented by the following general formulas (2) and (3).
[0041] [ka] [ka]
[0042] In formulas (2) and (3), n and m represent the number of repeating units, and are an average of 0 to 10. In formulas (2) and (3), the methylene group is a group bonded to the 2nd or 3rd position of the aromatic ring, and one or more R are substituents bonded to any position to which a methylene group is not bonded. Examples of R include alkyl groups and aryl groups having 1 to 20 carbon atoms.
[0043] The content of the polyfunctional maleimide compound (B) in the composition is preferably 5 to 80 parts by mass relative to 100 parts by mass of the thermosetting resin (A). If the content of the polyfunctional maleimide compound (B) is 5 parts by mass or more, the solder crack resistance and heat resistance will be even more excellent. From the same viewpoint, the content of the polyfunctional maleimide compound (B) is more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more. Furthermore, if the content of the polyfunctional maleimide compound (B) is 80 parts by mass or less, the adhesiveness will be even more excellent. From the same viewpoint, the content of the polyfunctional maleimide compound (B) is more preferably 60 parts by mass or less, and even more preferably 40 parts by mass or less.
[0044] 1-1c. Benzoxazine compounds (C) The benzoxazine compound (C) is a compound having a benzoxazine ring in the molecule. The benzoxazine compound (C) is not particularly limited, but from the viewpoint of crosslinkability, curability, etc., a compound having two or more benzoxazine rings in one molecule is preferred. Specific examples of the benzoxazine compound include Fa-type benzoxazine compounds obtained by reacting a bisphenol compound with an amine compound (e.g., aniline) and formaldehyde, such as bisphenol A-type benzoxazine compounds and bisphenol F-type benzoxazine compounds, and Pd-type benzoxazine compounds obtained by reacting a phenyldiamine compound with a phenol compound and formaldehyde, such as diaminodiphenylmethane-type benzoxazine compounds. These compounds are commercially available and can be used. These compounds are non-polymers. Among the Fa-type benzoxazine compounds and the Pd-type benzoxazine compounds, the Pd-type benzoxazine compounds are preferred from the viewpoint of superior heat resistance.
[0045] For example, a bisphenol F benzoxazine compound, which is an Fa benzoxazine compound, has a structure as shown in the following formula (4), which is obtained by reacting bisphenol F, aniline, and formaldehyde. [ka]
[0046] For example, a Pd-type benzoxazine compound has a structure as shown in the following formula (5), which is obtained by reacting 4,4'-methylenedianiline, phenol, and formaldehyde. [ka]
[0047] The content of the benzoxazine compound (C) in the composition is preferably 1 to 50 parts by mass relative to 100 parts by mass of the thermosetting resin (A). If the content of the benzoxazine compound (C) is 1 part by mass or more, flame retardancy can be further improved. From the same viewpoint, the content of the benzoxazine compound (C) is more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more. Furthermore, if the content of the benzoxazine compound (C) is 50 parts by mass or less, the brittleness of the sheet can be reduced, and conformability to electronic components can be easily improved. From the same viewpoint, the content of the benzoxazine compound (C) is more preferably 45 parts by mass or less, and even more preferably 40 parts by mass or less.
[0048] 1-1d. Epoxy resin (D) The epoxy resin (D) is not particularly limited as long as it is a resin having an epoxy group in the molecule. Trifunctional or higher polyfunctional epoxy resins are useful for improving the heat resistance and adhesion of the coating film, and bifunctional epoxy resins such as bisphenol A and bisphenol F, which will be described later, are useful when flexibility of the coating film is required. The epoxy resin (D) may be composed of only trifunctional epoxy resins, or may be composed of a combination of a trifunctional epoxy resin with a bifunctional or monofunctional epoxy resin.
[0049] Examples of the epoxy resin (D) include bisphenol-type epoxy resins, triphenylmethane-type epoxy resins, novolac-type epoxy resins, alicyclic epoxy resins, glycidyl esters, glycidyl amines, heterocyclic epoxy resins, and brominated epoxy resins.
[0050] Examples of bisphenol type epoxy resins include bisphenol A type epoxy resins, bisphenol F type epoxy resins, and bisphenol S type epoxy resins. Examples of the phenylmethane type epoxy resin include diphenylmethane type epoxy resin and triphenylmethane type epoxy resin. Examples of novolac epoxy resins include phenol novolac epoxy resins, cresol novolac epoxy resins, bisphenol A novolac epoxy resins, and dicyclopentadiene novolac epoxy resins. Examples of the alicyclic epoxy resin include 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 1-epoxyethyl-3,4-epoxycyclohexane. Examples of the glycidyl esters include diglycidyl phthalate, diglycidyl tetrahydrophthalate, and glycidyl dimerate. Examples of glycidylamines include tetraglycidyldiaminodiphenylmethane, triglycidyl p-aminophenol, and N,N-diglycidylaniline. Examples of heterocyclic epoxy resins include 1,3-diglycidyl-5,5-dimethylhydantoin and triglycidyl isocyanurate. Examples of brominated epoxy resins include tetrabromobisphenol A type epoxy resins, tetrabromobisphenol F type epoxy resins, brominated cresol novolac type epoxy resins, and brominated phenol novolac type epoxy resins.
[0051] The content of the epoxy resin (D) in the composition is preferably 1 to 50 parts by mass per 100 parts by mass of the thermosetting resin (A). If the content of the epoxy resin (D) is 1 part by mass or more, the adhesiveness will be even better. From the same viewpoint, the content of the epoxy resin (D) is more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more. Furthermore, if the content of the epoxy resin (D) is 50 parts by mass or less, the protection of electronic components will be even better. From the same viewpoint, the content of the epoxy resin (D) is more preferably 45 parts by mass or less, and even more preferably 40 parts by mass or less.
[0052] The total content of the polyfunctional maleimide compound (B), benzoxazine compound (C), and epoxy resin (D) in the composition is preferably 5 to 180 parts by mass per 100 parts by mass of the thermosetting resin (A). When the total content of these components is 5 parts by mass or more, solder crack resistance and adhesiveness are further improved. From the same viewpoint, the total content of these components is more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, and particularly preferably 60 parts by mass or more. Furthermore, when the total content of these components is 180 parts by mass or less, penetration of the resin sheet into the hollow portion can be easily suppressed, and adhesiveness is further improved. From the same viewpoint, the total content of these components is more preferably 160 parts by mass or less, even more preferably 140 parts by mass or less, particularly preferably 120 parts by mass or less, and most preferably 100 parts by mass or less.
[0053] The above-mentioned components (B) to (D) can be mixed in a premixed state with other components (e.g., thermosetting resin (A) etc.) or can be melt-mixed by applying heat (e.g., 100°C or higher).
[0054] 1-1e. Other ingredients Inorganic filler (E) The composition may contain an inorganic filler (E) such as a metal oxide. Examples of the inorganic filler (E) include inorganic compounds such as silica, alumina, magnesium hydroxide, barium sulfate, calcium carbonate, titanium oxide, zinc oxide, antimony trioxide, magnesium oxide, talc, kaolinite, mica, basic magnesium carbonate, sericite, montmorillonite, kaolinite, bentonite, boron nitride, aluminum nitride, titanium nitride, and carbon black. Among these, from the viewpoint of coating film resistance to scratches, titanium oxide, titanium nitride, silica, talc, mica, kaolinite, or montmorillonite is preferred, titanium oxide, titanium nitride, and silica are more preferred, and silica is particularly preferred. In the present composition, the silica is particularly preferably in particulate form, and silica particles are preferably included. In the present disclosure, from the viewpoint of coating film resistance, two or more types of inorganic fillers may be contained.
[0055] The average primary particle size (hereinafter referred to as particle size) of the inorganic filler (E) is preferably 0.1 to 50 μm. By setting the particle size to 0.1 μm or more, it is easy to maintain the viscosity of the resin composition at a level suitable for coating. Furthermore, by setting the particle size to 50 μm or less, the smoothness of the coating film is further improved. The particle size of the inorganic filler (E) can be determined from the average value of approximately 20 primary particles observed in an image magnified approximately 50,000 to 1,000,000 times using a transmission electron microscope (TEM).
[0056] The inorganic filler (E) may be mixed with the thermosetting resin (A) after mechanical crushing, and the mixture may then be further dispersed. A dispersant is preferably used for the dispersion treatment. The dispersant can impart repulsive forces between the inorganic fillers so that the inorganic fillers dispersed through the dispersion treatment described above do not re-aggregate. The dispersant may be a conventionally known compound. Examples include polymeric dispersants, pigment derivative dispersants, and surfactants selected from cationic, anionic, and nonionic surfactants. The Mw of these dispersants is, for example, about 1,000 to 30,000.
[0057] The content of the inorganic filler (E) in the present composition (solid content) is preferably 5 to 70% by mass. If the content of the inorganic filler (E) is 5% by mass or more, it is possible to easily prevent the resin sheet from entering the hollow portion, and furthermore, solder crack resistance is more excellent. From the same viewpoint, the content of the inorganic filler (E) is more preferably 10% by mass or more. Furthermore, if the content of the inorganic filler (E) is 70% by mass or less, adhesion and solder crack resistance are more excellent. From the same viewpoint, the content of the inorganic filler (E) is more preferably 60% by mass or less.
[0058] The composition may contain a curing accelerator to adjust the crosslinking rate during the curing treatment or the physical properties of the resin sheet. The curing accelerator is not particularly limited and can be selected appropriately. Specific examples of the curing accelerator include amine-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. These may be used alone or in combination of two or more. From the viewpoint of coating suitability, the content of the curing accelerator in the present composition (solid content) is preferably 0.01 to 10 mass %, more preferably 0.1 to 5 mass %.
[0059] Various additives may be added to the composition without departing from the spirit of the present disclosure. For example, thermally conductive fillers may be used. Furthermore, additives such as antistatic agents, flame retardants, antioxidants, UV inhibitors, colorants, dispersants, surface conditioning additives, cure retarders, softeners, antiblocking agents, adhesion improvers, and embedding improvers may be added as appropriate.
[0060] 2. Hollow electronic components 1(a), a hollow electronic component 10 of the present disclosure (hereinafter also referred to as the present hollow electronic component) includes a substrate 1, an electronic component 2 mounted on the substrate 1, and a sealing layer 4 that seals the electronic component 2 while maintaining a hollow structure 3 between the substrate 1 and the electronic component 2. Here, in the present hollow electronic component, the sealing layer 4 is formed from a cured product of the above-described resin sheet for sealing hollow electronic components of the present disclosure. The method for manufacturing the hollow electronic component is not particularly limited, and conventionally known methods can be applied, but by using the resin sheet, it is possible to collectively cover multiple electronic components 2, such as semiconductor elements, mounted on a substrate 1 while maintaining the hollow structure 3. Specifically, the resin sheet is temporarily attached to the multiple electronic components 2, and the resin sheet is softened by heating and / or pressurizing, thereby covering and bonding the top surface of the substrate 1 and the top and side surfaces of the multiple electronic components 2 while maintaining the hollow structure 3. The resin sheet is then cured to form a sealing layer 4 that seals the electronic components 2, thereby obtaining the hollow electronic component. In this case, the resin sheet may be a single layer or multiple layers of the resin sheet of the present disclosure. Furthermore, as shown in FIG. 1(b), the hollow electronic component may have a sealing layer (first sealing layer) 4 made of the cured resin sheet coated with a second sealing layer 5 in tablet, liquid, granular, or sheet form, for example, to secondary seal the substrate 1 and electronic component 2. In this way, the hollow electronic component may have multiple sealing layers sealing the electronic component 2. [Example]
[0061] The present disclosure will be specifically described below with reference to examples and comparative examples, but the present disclosure is not limited to these examples. In the following description, "parts" and "%" represent "parts by mass" and "% by mass", respectively, unless otherwise specified.
[0062] 1. Resin sheets for sealing hollow electronic components (hereinafter referred to as resin sheets) The raw materials used in each example are listed below.
[0063] 1-1.Thermosetting resin (A) [Synthesis of thermosetting resin a1] [Synthesis of polyester diol] A glass flask equipped with a stirrer, thermometer, reflux condenser, nitrogen inlet, and pressure reducing equipment was charged with 266 parts of terephthalic acid, 30 parts of adipic acid, 212 parts of 3-methyl-1,5-pentanediol, and 25 parts of ethylene glycol, and stirred under nitrogen gas. The mixture was gradually heated under normal pressure and reacted at 200-230°C for approximately 8 hours, yielding a liquid with an acid value of 43 mgKOH / g. Next, 0.01 parts of tetra-n-butoxytitanium was added, and after nitrogen substitution, the mixture was stirred at 180°C for 30 minutes in a sealed container. The mixture was then reacted for 2 hours at 230°C and 5 mmHg, yielding a polyester diol with an acid value of 1.1 mgKOH / g, a hydroxyl value of 114.2 mgKOH / g, and a molecular weight of 982. The acid value and hydroxyl value were determined by weighing the thermosetting resin, measuring it using an automatic titrator GT-200 (product name) manufactured by Mitsubishi Chemical Analic Corporation in accordance with the potentiometric titration method of JIS K0070, and converting it into a solid content.
[0064] [Synthesis of urethane prepolymer] Next, 734 parts of the polyester diol, 23.9 parts of dimethylolpropionic acid, 219 parts of toluene diisocyanate, and 242 parts of toluene were placed in a reaction vessel equipped with a stirrer, thermometer, reflux condenser, dropping device, and nitrogen inlet tube, and reacted for 8 hours at 50° C. under a nitrogen atmosphere. To this was added 1,200 parts of toluene to obtain a urethane prepolymer solution having isocyanate groups at its terminals.
[0065] [Synthesis of urethane polymer] The resulting urethane prepolymer solution was then heated to 70°C, and while maintaining that temperature, a solution containing 20.0 parts of 1,3-diaminopropane, 600 parts of 2-propanol, and 961 parts of toluene was added dropwise over 1 hour. After the addition was completed, the mixture was allowed to react at 70°C for an additional 6 hours, yielding a polyurethane resin (thermosetting resin a1) with a molecular weight (Mw) of 130,000, an acid value of 10 mgKOH / g, a Tg of 20°C, and a solids content of 25%.
[0066] 1-2. Maleimide complex compound (mixture of components (B) to (D)) [Preparation of maleimide conjugate compounds m1 to m4] The following compounds were prepared as maleimide composite compounds containing a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D). Maleimide conjugate compound m1: "HR3053 (product name)", manufactured by Printec Co., Ltd. Maleimide conjugate compound m2: "HR-YSP (product name)", manufactured by Printec Co., Ltd. Maleimide complex compound m3: "HR3070 (product name)", manufactured by Printec Co., Ltd. Maleimide conjugate compound m4: "HR3072 (product name)", manufactured by Printec Co., Ltd.
[0067] 1-3.Epoxy resin (D) [Preparing epoxy resins d1 to d3] The following compounds were prepared as epoxy resins: Epoxy resin d1: Trifunctional epoxy compound "VG3101L (product name)", epoxy equivalent weight 210g / eq, manufactured by Printec Co., Ltd. Epoxy resin d2: Difunctional epoxy compound "EPICLON 840 (trade name)", epoxy equivalent weight 190 g / eq, containing hydroxyl groups, manufactured by DIC Corporation Epoxy resin d3: Novolac type epoxy compound "MEH-7851-SS (trade name)", epoxy equivalent 105 g / eq, manufactured by Nippon Kayaku Co., Ltd.
[0068] 1-4. Additives The following compounds were prepared as additives: Additive F1: Carbodiimide compound "Carbodilite V-01 (trade name)", epoxy equivalent 105 g / eq, manufactured by Nisshinbo Chemical Inc. Additive f2: Imidazole compound "Curezol 2E4MZ (product name)" manufactured by Shikoku Chemicals Co., Ltd. Additive f3: Silane coupling agent "KBM403 (product name)", manufactured by Shin-Etsu Chemical Co., Ltd.
[0069] 1-5. Inorganic filler (E) [Preparation of inorganic fillers e1 and e2] The following compounds were prepared as inorganic fillers. Inorganic filler e1: "Hypresilica TSN3N (trade name)", D 50 =2.0 μm, manufactured by Ube Exsymo Co., Ltd. Inorganic filler e2: "Mitsubishi Carbon Black MA-8 (product name)", D 50 =24nm, manufactured by Mitsubishi Chemical Corporation
[0070] 2.Measurement method 2-1. Breaking elongation The resin sheets with release films obtained in each of the Examples and Comparative Examples using the method described below were cut into pieces measuring 20 mm wide x 60 mm long. The release films were then peeled off to obtain measurement samples (electronic component covering sheets). The measurement samples were placed in a temperature of 100°C (in air, 50% RH), and one minute later, a tensile test was performed at that temperature at a tension rate of 50 mm / min using a small benchtop testing machine, EZ-TEST (trade name, manufactured by Shimadzu Corporation), with an effective tensile size of 20 x 17 mm, to determine the breaking elongation (%).
[0071] 2-2. Coefficient of linear expansion (CTE) The resin sheets with release film from each Example and Comparative Example were cured at 180°C for 2 hours, and the release film was then peeled off. They were cut into pieces 4 mm wide x 20 mm long, and their displacement was measured using a TA Instruments TMA Q400 under a 1 g load at a heating rate of 6°C / min from 0°C to 300°C. The linear expansion coefficient was calculated by averaging the slope between 150 and 200°C when the sample temperature was plotted on the horizontal axis and the displacement on the vertical axis.
[0072] 2-3.Adhesive strength The resin sheets with release films obtained in each Example and Comparative Example, as described below, were cut to a size of 90 mm x 90 mm. Two 50 μm-thick polyimide films ("Kapton 200EN" (product name) manufactured by Toray DuPont Co., Ltd.) were also prepared. The release films were peeled off from the electronic component covering sheets. The polyimide films were then temporarily attached to both sides of the electronic component covering sheets at 90°C, 0.3 MPa, and 1 m / min, respectively. Then, the sheets were heat-pressed at 100°C, 1.0 MPa, and 3 min, followed by curing at 180°C for 2 hours. Test pieces measuring 10 mm wide and 90 mm long were cut from the cured samples. A 90-degree peel test was performed using a small benchtop testing machine (EZ-TEST, manufactured by Shimadzu Corporation) at 25°C and 50% RH, with a pulling rate of 50 mm / min, to measure the adhesive strength A (N / cm).
[0073] 2-4. Glass transition temperature Tg The Tg of the measurement samples (electronic component covering sheets) of each example and comparative example was measured using a dynamic viscoelasticity measuring device DVA-200 (trade name, manufactured by IT Measurement & Control Co., Ltd.) in accordance with JIS K7198. For the measurement, the resin sheet with release film of each example was cured at 180°C for 2 hours, cut to a 0.5 cm x 3 cm piece, and the release film was removed. The Tg was determined as the temperature at which the main dispersion peak of the loss tangent (tanδ) appeared, measured under tensile deformation conditions of 0.08%, a frequency of 10 Hz, a heating rate of 10°C / min, and a temperature range of -50°C to 300°C. Note that in multilayer covering sheets, multiple maximum values of the loss tangent (tanδ) may exist. In such cases, the highest temperature was designated as the Tg (°C) of the sample.
[0074] 3. Preparation of Resin Sheet [Example 1] A container was charged with 100 parts of thermosetting resin a1 (solids), 3 parts of maleimide composite compound m1 (HR3053), 0.8 parts of additive f1 (Carbodilite V-01), 0.1 parts of additive f2 (2E4MZ), 45 parts (30% by mass) of inorganic filler e1, and 0.8 parts (0.5% by mass) of inorganic filler e2. Toluene was then added to the container to achieve a nonvolatile content of 33% by mass, and the mixture was stirred with a disperser for 10 minutes to obtain a composition. This composition was applied to a release film (release-treated polyethylene terephthalate film, 50 μm thick) using a doctor blade to a dry thickness of 20 μm. The resulting coating was then dried at 100°C for 2 minutes to obtain a resin sheet with a release film having a single layer (first layer) configuration.
[0075] [Examples 2 to 24, Comparative Examples 1 and 2] Resin sheets with release films according to Examples 2 to 24 and Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that the composition formulation was changed as shown in Tables 1 and 2.
[0076] Tables 1 and 2 below show the formulations of the examples and comparative examples. [Table 1] [Table 2]
[0077] 4. Preparation of a test SAW chip mounting substrate (hereinafter referred to as test substrate 20) A test substrate 20 was prepared by mounting SAW chips (1.2 mm long, 1.2 mm wide, 0.2 mm high (200 μm)) as electronic components 12 in five columns and five rows at 0.2 mm (200 μm) spacing on a glass epoxy FR-4 substrate 11 (80 mm long, 80 mm wide, 0.25 mm high). The SAW chips were bonded to the FR-4 substrate using lead-free solder balls 13 (50 μm high). The SAW chips were bonded to the FR-4 substrate at four corners, positioned 0.1 mm inward from the edges of the SAW chip, at 200°C (see Figure 2). Figure 2 is a schematic diagram of the test substrate of this example, with Figure 2(a) showing a top view (plan view) and Figure 2(b) showing a front cross-sectional view.
[0078] 5. Evaluation The resin sheet with release film of each Example and Comparative Example was placed so that the resin sheet side of the resin sheet with release film was placed on a test substrate, and thermocompression bonded under conditions of 100°C, 0.1 MPa, and 1 minute. After that, the release film was peeled off, and then thermocompression bonded under conditions of 100°C, 0.5 MPa, and 3 minutes. Heating was carried out at 180°C for 2 hours to obtain a test substrate covered with a resin sheet (test substrate with resin sheet). The obtained test substrate with resin sheet was evaluated as follows.
[0079] 5-1.SAW chip protection The test substrate with the resin sheet was polished to form a cross section, allowing observation of the state of the resin sheet covering the SAW chip and the state of the SAW filling the hollow portion. Ten randomly selected SAW chips were observed under an electron microscope (magnification 400x), and the degree of protection of the SAW chips was judged according to the following criteria.
[0080] 5-1-1.SAW chip coverage The state of the resin sheet covering the SAW chips was observed, and the number of SAW chips that were entirely covered with the resin sheet was counted and evaluated according to the following criteria. Evaluation criteria A: The number of SAW chips covered with the resin sheet is 10. B: The number of SAW chips covered with the resin sheet is 8 to 9. C: The number of SAW chips covered with the resin sheet is 6 to 7. D: The number of SAW chips covered with the resin sheet is 4 to 5. E: The number of SAW chips covered with the resin sheet is 3 or less. Not suitable for practical use.
[0081] 5-1-2.SAW hollow part penetration The state of penetration of the resin sheet into the hollow portion of the SAW chip was observed, and the number of SAW chips in which the solder balls at the bottom of the SAW chip were in contact with the resin sheet was counted and evaluated according to the following criteria. Evaluation criteria A: The number of SAW chips where the resin sheet is in contact with the solder balls is 0. B: The number of SAW chips in which the resin sheet is in contact with the solder balls is 1 to 2. C: The number of SAW chips in which the resin sheet is in contact with the solder balls is 3 to 4. D: The number of SAW chips in which the resin sheet is in contact with the solder balls is 5 to 6. E: The number of SAW chips in which the resin sheet is in contact with the solder balls is 7 or more. Not suitable for practical use.
[0082] 5-2. Solder crack resistance after thermal shock test The test substrate with the resin sheet was placed in a thermal shock chamber TSA-43EL (trade name, manufactured by ESPEC Corporation), and subjected to a thermal shock test with 1000 cycles of exposure from -50°C to 125°C, with each temperature exposure time being 10 minutes. After the test, the test substrate with the resin sheet was polished to form a cross section so that the condition of the solder balls below the SAW chips could be observed. Ten random SAW chips were observed under an electron microscope (magnification 400x), and cracks occurring in the solder balls below the SAW chips were evaluated according to the following criteria. Evaluation criteria A: The number of SAW chips with cracks in the solder balls is 0. B: The number of SAW chips with cracks occurring in the solder balls is 1 to 2. C: The number of SAW chips with cracks occurring in the solder balls is 3 to 4. D: The number of SAW chips with cracks in the solder balls is 5 to 6. E: The number of SAW chips with cracks in the solder balls is 7 or more. Not suitable for practical use.
[0083] 5-3. Adhesion after thermal shock test The test substrate with the resin sheet was placed in a thermal shock chamber TSA-43EL (trade name, manufactured by ESPEC Corporation), and subjected to a thermal shock test with 1000 cycles of exposure from -50°C to 125°C, with each temperature exposure time being 10 minutes. After the test, the test substrate with the resin sheet was polished to form a cross section so that the bond between the resin sheet and the SAW chip could be observed. Ten random SAW chips were observed under an electron microscope (magnification 400x), and the occurrence of delamination between the resin sheet and the SAW chip was judged according to the following criteria. Evaluation criteria A: The number of SAW chips in which peeling of the resin sheet occurred is 0. B: The number of SAW chips in which peeling of the resin sheet occurred was 1 to 2. C: The number of SAW chips in which peeling of the resin sheet occurred was 3 to 4. D: The number of SAW chips in which peeling of the resin sheet occurred was 5 to 6. E: The number of SAW chips in which peeling of the resin sheet occurred was 7 or more. Not suitable for practical use.
[0084] The physical properties and evaluation results of each of the Examples and Comparative Examples are shown in Tables 3 and 4 below. [Table 3] [Table 4]
[0085] In Comparative Example 2, which did not contain the thermosetting resin (A), and Comparative Examples 1 and 2, which did not contain the polyfunctional maleimide compound (B) and the benzoxazine compound (C), flexibility and adhesive strength were inferior to those of the other Examples, and it was confirmed that there were problems with SAW chip protection and adhesiveness after thermal shock tests. In other words, it was found that it was difficult to achieve both excellent flexibility and low thermal expansion in these Comparative Examples.
[0086] On the other hand, the resin sheet containing a thermoplastic resin (A), a polyfunctional maleimide compound (B), a benzoxazine compound (C), and an epoxy resin (D) exhibited excellent SAW chip protection, and also exhibited good solder crack resistance and adhesion after thermal shock testing. Furthermore, the resin sheets shown in Examples 6 to 8 and 13 to 15 were evaluated as A in all categories, demonstrating their particularly excellent performance.
[0087] The present disclosure is not limited to the above-described embodiment, and can be appropriately modified without departing from the spirit and scope of the present disclosure. Furthermore, the present disclosure may be implemented by appropriately combining the above-described embodiment and examples thereof. [Explanation of symbols]
[0088] 1, 11 board 2, 12 Electronic Components 3 Hollow structure 4. Sealing layer (first sealing layer) 5 Second sealing layer 6, 13 Solder ball 10 Hollow electronic components 20 Test board
Claims
1. A resin sheet for sealing hollow electronic components, for forming a sealing layer of a hollow electronic component, The resin sheet for sealing hollow electronic components is a resin composition containing a polyurethane resin, a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D).
2. 2. The resin sheet for sealing hollow electronic components according to claim 1, wherein a total content of the polyfunctional maleimide compound (B) having two or more maleimide groups, the benzoxazine compound (C), and the epoxy resin (D) in the resin composition is 5 to 180 parts by mass relative to 100 parts by mass of the polyurethane-based resin.
3. The resin sheet for sealing hollow electronic components according to claim 1 , wherein the resin composition further comprises an inorganic filler (E), and the inorganic filler (E) comprises silica particles.
4. The resin sheet for sealing hollow electronic components according to claim 3, wherein the content of the inorganic filler (E) in the resin composition is 5 to 70 mass%.
5. 2. The resin sheet for sealing hollow electronic components according to claim 1, wherein the resin sheet is cured at 180 ° C. for 2 hours and the cured product has a linear expansion coefficient at 150 to 200 ° C. of 3 to 750 ppm / K.
6. The resin sheet for sealing hollow electronic components according to claim 1, wherein the breaking elongation at 100°C is 300 to 2000%.
7. 2. The resin sheet for sealing hollow electronic components according to claim 1, wherein the resin sheet is bonded to a polyimide substrate and cured at 180 ° C. for 2 hours, and the cured product has an adhesive strength of 0.6 to 40 N / cm at 25 ° C. The resin sheet for sealing hollow electronic components according to claim 1.
8. A hollow electronic component comprising: a substrate; an electronic component mounted on the substrate; and a sealing layer that seals the electronic component while maintaining a hollow structure between the substrate and the electronic component, wherein the sealing layer is formed from a cured product of the resin sheet for sealing hollow electronic components according to any one of claims 1 to 7.
Citation Information
Patent Citations
Heat curing resin sheet for sealing, electronic component device, and method of manufacturing electronic component device
JP2008177432A
Electronic device
JP2020145270A
Silicon carbide, gallium oxide, gallium nitride, and molding material composition for sealing diamond element, and electronic component device
JP2020145424A
Resin sheet for sealing
JP2021097206A
Thermosetting sealing sheet and method for manufacturing sealing body of mounting structure
JP7541174B1